A Structural Calculation Model of Shield Tunnel Segment: Heterogeneous Equivalent Beam Model. (26th August 2018) - Lei, Mingfeng; Lin, Dayong; Shi, Chenghua; Ma, Jianjun; Yang, Weichao
Abstract : A heterogeneous equivalent beam model (HEB model) of the shield tunnel segment structure is proposed based on a systematical analysis on the stress state of the cross section of segment joints. This model treats a noncontinuous segment structure as a continuous heterogeneous structure, on the basis of the principle of equivalent stress state on a section and equivalent conversion of the mechanical parameters. For a comprehensive demonstration of the proposed HEB model, an interpretative solution of equivalent mechanical parameters of the joint section is obtained through theoretical derivation, and a specific iterative computation flow is provided in accordance. Model validation and comparative analysis are also conducted for two industrial applications. It is found that the iterative process of calculation has good convergence, leading to reliable numerical results for all cases under consideration. Resulting simulations reveal that the proposed HEB model can reflect the effect of joints on overall rigidity of a segment structure. Compared with the computation results obtained using other models presented in the literature, there are smaller axial force deviation and larger bending moment deviation (up to 20% or higher), demonstrating that the model selection is important in design and computation of a segment structure of shield tunnels. The proposed model and analysis for model performance may provide useful reference for engineers in shield tunnel community.